How Two-Child Policy Affects China's Energy Consumption: The Mediating Role of Lifestyle - Chen, Fengzhang; Wang, Wei; Wang, Yanfei; Wu, Yongqiu (Frontiers in Public Health, 2022)
Background Existing literature believed that the birth control policy affects energy consumption through the change in population size, but ignored the changes in people's lifestyle. This may mislead the government's policy-making about population and energy consumption. Method This article proposed a Population-Lifestyle-Energy (PLE) model to provide new insights into how birth control policy affects energy consumption if the changes in people's lifestyle are considered. The ProFamy software is used to forecast the changes in demographic characteristics. The methods of regression analysis and Input-Output Analysis are used to predict the impacts of lifestyle changes on energy consumption. Results We find that China's two-child policy will result in the total energy consumption increase by 16.2% in 2050, far outpacing the population increase of 9.3% when considering the indirect effect of lifestyle changes. This is significantly different from the optimistic wisdom in the existing literature. We also find the non-linear relationships between fertility rate and energy consumption. Conclusion Ignoring lifestyle changes will lead to an underestimation of energy consumption. Contrary to conventional optimistic wisdom, we believe that the two-child policy will make it difficult for China to meet promised energy conservation goals.